Teaching strategies supported by digital communication tools in social networks - Delgado Vaca Guzmán, Lizzie Mary; Castro Onofre, Juan Carlos; Orosco Tejerina, Oscar (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Social networks have become an effective means of digital interaction of people. Thus, education assumes them in order to adapt them to the teaching-learning process by applying them under an asynchronous interaction between the student and the teacher, hence the research proposed as an objective the design of teaching strategies based on digital communication tools. in social networks, whose main conclusion was the verification of the efficiency of teaching strategies based on digital communication tools in social ne0tworks on the teaching-learning process.